DEVELOPING SECONDARY STUDENTS’ COMMUNICATIVE COMPETENCE: POLITICS AND REALITY - Halbach, Ana (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract That theory and practice do not always go hand in hand is something of a commonplace. The same holds true for what is legislated about how languages should be taught, and how they really are taught in schools. This relation between politics and classroom reality is the topic of the present paper. In it secondary school teachers' attitude towards language teaching and students' perception of the way in which languages are taught are compared with what, according to government policies should be going on in classrooms. At the end of the paper, possible reasons for the divergence between one and the other are forwarded.